Pengaruh Kualitas Pelayanan Dan Iklim Organisasi Terhadap Kepuasan Nasabah Pada Bank BRI Unit Maligano Kecamatan Maligano Kabupaten Muna - Santi M, Santi M; jopang, jopang; nurjannah, nurjannah (Universitas Halu Oleo, 2017)
This study aims to examine how much the influence of Service Quality and Organizational Climate on Customer Satisfaction at the BRI Bank Maligano Unit, Maligano District, Muna Regency The independent variable consists of Service Quality (X1) and Organizational Climate (X2). Dependent Variable is Customer Satisfaction (Y) at BRI Bank Maligano Unit, Maligano District, Muna Regency. The number of research samples is 86 respondents taken using accidental sampling technique. The analysis used is Multiple Linear Regression Analysis whose results are Y = 2.984 + 0.102 + 0.18 + 1,185. The most independent variable influencing the dependent variable is the Service Quality variable of (2.659) and followed by the organizational climate variable (0.198). The coefficient of determination (R2) of 0.318 or 31.8% means that the coefficient of determination model is not good.This research was conducted by distributing quoisier to several customers of the BRI Bank Maligano Unit, Maligano District, Muna Regency by accidental sampling and analyzed by Multiple Linear Regression. This model emphasizes the influence of the Organizational Services Quality and Climate on Customer Satisfaction whose analysis results are processed using SPSS Version 16.The results of this study indicate that there are two hypotheses that have been tested in this study, namely Service Quality and Organizational Climate. Where both of these hypotheses have positive and significant influence on Customer Satisfaction at the BRI Bank Maligano Unit, Maligano District, Muna Regency. The results showed that this research model was acceptable.